Caveolin-1 Regulates Cellular Metabolism: A Potential Therapeutic Target in Kidney Disease - Luo, Shilu; Yang, Ming; Zhao, Hao; Han, Yachun; Jiang, Na; Yang, Jinfei; Chen, Wei; Li, Chenrui; Liu, Yan; Zhao, Chanyue; Sun, Lin (Frontiers in Pharmacology, 2021)
The kidney is an energy-consuming organ, and cellular metabolism plays an indispensable role in kidney-related diseases. Caveolin-1 (Cav-1), a multifunctional membrane protein, is the main component of caveolae on the plasma membrane. Caveolae, are represented by tiny invaginations that are abundant on the plasma membrane and which serve as a platform to regulate cellular endocytosis, stress responses and signal transduction. However, caveolae have received increasing attention as a metabolic platform that mediates the endocytosis of albumin, cholesterol and glucose, participates in cellular metabolic reprogramming and is involved in the progression of kidney disease. It is worth noting that caveolae mainly depend on Cav-1 to perform the abovementioned cellular functions. Furthermore, the mechanism by which Cav-1 regulates cellular metabolism and participates in the pathophysiology of kidney diseases has not been completely elucidated. In this review, we introduce the structure and function of Cav-1 and its functions in regulating cellular metabolism, autophagy and oxidative stress, focusing on the relationship between Cav-1 in cellular metabolism and kidney disease. In addition, Cav-1 serves as a potential therapeutic target for treatment of kidney disease is also described.